2005
DOI: 10.1038/sj.gene.6364169
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms within the PHF11 gene at chromosome 13q14 are associated with childhood atopic dermatitis

Abstract: Atopic dermatitis is an increasingly common and debilitating childhood disorder that is often accompanied by asthma and allergic rhinitis. Although the pathology of these disorders is distinct, the majority of cases are atopic, typified by elevated serum IgE. A new locus at chromosome 13q14 centred on the genes SETDB2 and PHF11 and associated with increased total serum IgE has recently been identified. Although the precise functions of SETDB2 and PHF11 are not known, both proteins are expressed in cells of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 15 publications
3
30
1
1
Order By: Relevance
“…The strong association of H3 K9 3m with the S regions after stimulation suggests that it may have a role in the regulation of CSR. This proposition is supported by recent reports linking two H3 K9 methyltransferase enzymes with switching to specific isotypes or Ig serum levels and human disease: Suv39h1 is linked to switching to IgA (56), whereas SETDB2 is linked to serum IgE levels and atopic dermatitis (57,58).…”
Section: Discussionsupporting
confidence: 71%
“…The strong association of H3 K9 3m with the S regions after stimulation suggests that it may have a role in the regulation of CSR. This proposition is supported by recent reports linking two H3 K9 methyltransferase enzymes with switching to specific isotypes or Ig serum levels and human disease: Suv39h1 is linked to switching to IgA (56), whereas SETDB2 is linked to serum IgE levels and atopic dermatitis (57,58).…”
Section: Discussionsupporting
confidence: 71%
“…For the genotyping of the samples, we acknowledge the University of Eastern Finland and the Mutation Analysis Core Facility at Karolinska Institutet. Thomas Dahllund, 11 Johanna Granvik, 12 Maarit Haapalehto-Ikonen, 13 AnuMaaria Hämäläinen, 14 Hanna Huopio, 15 Christian Johansson, 16 Anne Kinnala, 17 Jussi Korhonen, 18 Paavo Korpela, 19 Maarit Korteniemi, 20 Pentti Lautala, 21 Kaija Lindströ m, 22 Päivi Miettinen, 1 Taina Mustila, 23 Anja Nuuja, 24 Päivi Nykänen, 25 Jussi Ojanperä, 26 Anne Putto-Laurila, 5 Marja-Terttu Saha, 4 Juhani Sankila, 27 Anne-Maarit Suomi, 6 Sirpa Tenhola, 28 Pentti Varimo, 29 Riitta Veijola, 8 Ritva Virransalo, 30 Pentti Vuolukka, 31 …”
Section: Acknowledgmentsunclassified
“…We have recently shown that human GIMAP4 plays a role in Th cell secretory processes (27). Both GIMAP4 and GIMAP5 have been shown to be regulated by plant homeodomain finger protein 11 (28), polymorphisms of which affect total IgE, allergic asthma, and eczema (29,30). Moreover, most of the GIMAP family proteins are downregulated in the Tregs of T1D patients, possibly because of IL-2 deprivation (31).…”
mentioning
confidence: 99%
“…All of the regions have been previously found to be linked to asthma/atopic disease or related phenotypes, such as IgE titres (Iyengar et al, 2001;Jang et al, 2005;Kurz et al, 2006;Xu et al, 2001;Zhang et al, 2003). The novel regions of linkage were chromosome 5p15-p13 and 13q13-q22 linked with the number of P. falciparum clinical malaria attacks in Dielmo, and chromosome 12q21-q23 with the maximum parasite density during asymptomatic carriage in Ndiop.…”
Section: Genome Wide Linkage Analysis Of P Falciparum In Senegalmentioning
confidence: 99%